2023
DOI: 10.1002/jctb.7370
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the composting stages of green waste using the CIELAB color model

Abstract: BACKGROUNDCIELAB color variables can be used to monitor a composting process and evaluate the maturity of the compost with a new, rapid, easy, and low‐cost colorimetric analysis. However, to date there are no available data to support the ability of CIELAB color changes to depict the different stages of a composting procedure. This study aims to examine the correlation of CIELAB color variables with composting time to elucidate how color changes can be used to detect the different stages of a composting proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…In addition, the study by Tsivas et al (2023) showed that compost color had almost similar values and identical progression patterns when composting similar main organic substrates with different additives. However, the color variables appear to be influenced by the inherent properties of the raw materials (Tsivas et al 2023). In particular, different composting substrates exhibit different color values during composting (Khan et al 2009;Tsivas et al 2021).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In addition, the study by Tsivas et al (2023) showed that compost color had almost similar values and identical progression patterns when composting similar main organic substrates with different additives. However, the color variables appear to be influenced by the inherent properties of the raw materials (Tsivas et al 2023). In particular, different composting substrates exhibit different color values during composting (Khan et al 2009;Tsivas et al 2021).…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies (Khan et al 2009;Tsivas et al 2021;Tsivas et al 2023) have shown that compost color, and in particular the CIELAB color model, could partially mitigate typical compost physicochemical analyses and provide a rapid and more cost-effective method for monitoring composting. Compost color change has been shown to follow the evolution of composting (Khan et al 2009;Tsivas et al 2021), and, in particular, organic matter transformation (Tsivas et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations